Managing Vernal Keratoconjunctivitis in Children with Precision Medication: Case Report and Literature Review - Peggy Luisananda Dyaranggi; Oktarina Nila Juwita (Malahayati Nursing Journal, 2023)
ABSTRACT Vernal Keratoconjunctivitis is a chronic inflammatory condition that primarily affects the conjunctiva of both eyes. It is characterized by recurrent episodes of inflammation, often following a seasonal pattern, and is the result of a Type I hypersensitivity reaction. This condition is associated with specific clinical features, including the hypertrophy of papillae in the tarsal conjunctiva and limbus. There are two distinct forms of vernal conjunctivitis, the palpebral and limbal types, each presenting with its own set of clinical features and management considerations. In the case at hand, a 6-year-old male patient presented with active vernal conjunctivitis that had persisted continuously for the past four months. Despite receiving treatment with topical anti-inflammatory eye drops aimed at stabilizing the inflammatory response, the patient's condition did not show significant improvement. The diagnosis of vernal conjunctivitis was established through a thorough patient history evaluation. Additionally, an ophthalmological examination revealed clinical signs, such as ciliary injection (+), hyperemia (+), and pseudogerontoxon (+) in both eyes, further confirming the diagnosis. The management for patient during the acute phase of the disease included the administration of mast cell stabilizers. Topical corticosteroids were also considered to address the inflammation and alleviate the patient's symptoms. The combined therapy approach involving topical mast cell stabilizers and topical corticosteroids ultimately led to a noticeable improvement in the patient's clinical condition and relief from the troublesome symptoms of vernal conjunctivitis. This multidisciplinary management approach highlights the importance of tailoring treatment to the individual patient's needs, considering both the acute and long-term aspects of this chronic ocular condition. Keywords: Vernal Keratoconjunctivitis, Mast Cell Stabilizers, Topical Corticosteroids, Chronic Ocular Disorder.